An international congress. A different way of learning. (Journal of Parents and Teachers, 2014)
This article presents the experience of a school that traveled to Italy to present a paper at an international congress. It explains, in addition, in what consists the work and the objectives that they were following.
Keywords: Travel; Italy; international congress; learning; active methodologies; Jesuit colleges.